1999
DOI: 10.1097/00000421-199906000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Controlled Evaluation of Glutamine for Decreasing Stomatitis in Patients Receiving Fluorouracil (5-FU)-Based Chemotherapy

Abstract: Mucositis is a prominent dose-limiting toxicity associated with 5-FU-based chemotherapy. On the basis of preliminary data suggesting that the amino acid glutamine could alleviate this problem, the authors developed this trial. Patients scheduled to receive their first 5-FU-based chemotherapy regimen were selected for study. Following stratification, patients were randomized, in a double-blind manner, to receive oral glutamine or a placebo preparation in a prophylactic manner. Patients in both groups were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 11 publications
0
67
0
Order By: Relevance
“…The conclusions of this meta-analysis revealed that glutamine significantly reduced the risk and severity of oral mucositis induced by RT or CHRT compared with either placebo or no treatment (risk ratio 0.17; 95% CI 0.06-0.47) (21)(22)(23)(24)(25). Another systematic review of well-designed studies in various solid tumors and patients with hematological cancer revealed inadequate or conflicting evidence (26), as five studies did not find glutamine to be effective (27)(28)(29)(30), while four studies did (19,(31)(32)(33), suggesting a requirement for further studies on the use of oral glutamine to guide clinicians on which interventions are truly effective.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions of this meta-analysis revealed that glutamine significantly reduced the risk and severity of oral mucositis induced by RT or CHRT compared with either placebo or no treatment (risk ratio 0.17; 95% CI 0.06-0.47) (21)(22)(23)(24)(25). Another systematic review of well-designed studies in various solid tumors and patients with hematological cancer revealed inadequate or conflicting evidence (26), as five studies did not find glutamine to be effective (27)(28)(29)(30), while four studies did (19,(31)(32)(33), suggesting a requirement for further studies on the use of oral glutamine to guide clinicians on which interventions are truly effective.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies report reduced mucositis with glutamine (11)(12)(13) , while two report reduced subjective measures of mucositis (gut absorbtive capacity and endoscopic appearances) but no reduction in subjective symptoms of mucositis (14,15) . Three studies report no change in mucositis (16,17,19) . Neither of the two studies reporting infections (12,19) demonstrates a difference in the number of infections.…”
Section: Chemotherapy and Radiotherapymentioning
confidence: 99%
“…There is also a reduction in infections with intravenous glutamine. There is, however, an increase in relapse with intravenous Objective Cerchietti et al (12) Daniele et al (13) Huang et al (15) Jebb et al (16) Okuno et al (17) Peterson et al (18) Subtotal (95 % CI) Total events Heterogeneity: χ 2 5.24, df 4 (P=0·26); I 2 24 % Test for overall effect: Z 1·07 (P=0·28) Subjective Huang et al (15) Okuno et al (17) Subtotal (95 % CI) Total events Heterogeneity: χ 2 0·00, df 1 (P=1·00); I 2 0 % Test for overall effect: Z 0·45 (P=0·65) Objective Huang et al (15) Jebb et al (16) Okuno et al (17) Peterson et al (18) Subtotal ( glutamine but this result was based on two small studies (30,32) of patients undergoing autologous transplantation.…”
Section: Bone-marrow Transplantationmentioning
confidence: 99%
“…However, despite the previous positive trials, a large phase III trial testing oral glutamine with 5-fluorouracil (5-FU) chemotherapy did not show benefit [120]. One hundred and thirty four subjects, randomized to receive 4 g of glutamine twice a day, were instructed to retain the glutamine mouthwash in their mouths for only 10 seconds.…”
Section: Stomatitis/mucositismentioning
confidence: 99%